2018
DOI: 10.1111/1346-8138.14704
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics of spinal calcinosis in systemic sclerosis: Possible association with peripheral angiopathy

Abstract: The objective was to evaluate the demographic and clinical characteristics of systemic sclerosis (SSc) patients with spinal calcinosis. Paraspinal and intraspinal calcinosis was assessed blindly by orthopedic surgeons specializing in spinal diseases using chest high‐resolution computed tomography (CT) that was performed for the screening and prospecting of interstitial lung disease in 159 Japanese SSc patients. Among these patients, we identified 27 (17%) with spinal calcinosis, and the most common site was ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As described by Avouac et al [ 13 ] and Johnstone et al [ 38 ] we confirmed the combination of calcinosis, acro-osteolysis and periarticular calcifications with the presence of digital ulcers, which is more related to vascular disease. As suggested by Motegi and al [ 39 ] the development of spinal calcinosis may be associated with peripheral vasculopathy. With respect to erosions and joint space narrowing, these lesions were mainly observed on DIP and PIP joints whereas the MCP joints were spared, a classical finding usually observed in digital osteoarthritis and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 93%
“…As described by Avouac et al [ 13 ] and Johnstone et al [ 38 ] we confirmed the combination of calcinosis, acro-osteolysis and periarticular calcifications with the presence of digital ulcers, which is more related to vascular disease. As suggested by Motegi and al [ 39 ] the development of spinal calcinosis may be associated with peripheral vasculopathy. With respect to erosions and joint space narrowing, these lesions were mainly observed on DIP and PIP joints whereas the MCP joints were spared, a classical finding usually observed in digital osteoarthritis and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 93%
“…10 , 21 Spinal cord compression in scleroderma-associated calcinosis is rare. Motegi et al 8 report that of 159 patients with systemic scleroderma, 27 (17%) had spinal calcinosis. Of those with spinal calcinosis, 7 of 27 (25.9%) had spinal cord compression from calcinosis, which represents 4.4% of patients with systemic scleroderma who have spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…Of those with spinal calcinosis, 7 of 27 (25.9%) had spinal cord compression from calcinosis, which represents 4.4% of patients with systemic scleroderma who have spinal cord compression. 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations